Pendidikan Anti Korupsi Bagi Siswa SMA di Kabupaten Maluku Tengah - Ubwarin, Erwin; Salamor, Yonna Betrix; Leatemia, Wilshen; Salamor, Anna Maria (University of Muhammadiyah Malang, 2020)
Indonesia will get a demographic bonus in 2045 with a hundred years in the country, which means high school students, are people who will be productive and occupy strategic positions in 2045, both in government and non-government fields, what if they life in 2045 is a corrupt generation. Then the aim of this service is to carry out the tri dharma of tertiary institutions and to foster an anti-corruption culture for students. Methods of activities by doing design thinking, and socialization. The results of this dedication, the formation of students who have mental anti-corruption and become agents of reform in high school. The changes that occur are they begin to be ashamed to cheat, do not take things that do not have them, form an honesty canteen.